The Analysis of Placemaking in Religious-Based Regional Segregation - Marchella, Sabrina; Rembulan, Cicilia Larasati (Journal of Psychological Perspective, 2025)
Maluku is one of Indonesia's regencies, famous for having a harmonious inter-religious life, one of which is because of the panas pela tradition that binds its people to live side by side like brothers and sisters, regardless of differences in belief. However, in 1999 a conflict arose in Maluku and created tension between Christian and Muslim residents. The impact is still clearly visible today in the segregation of residential areas based on religion. Apart from that, a small portion of the Christian people still choose to live in the middle of Muslim settlements. The same thing also applies to a small portion of the Muslim people who still live in Christian residential areas. The purpose of this study was to determine the form of placemaking of Christians and Muslims to create a comfortable and safe place to live even though they are in the middle of a religious group that has been involved in conflict with them. This study was conducted through a qualitative design using interview and map elicitation methods involving 10 respondents. The results revealed three main forms of placemaking for Ambon city residents, namely building positive interactions with neighbors of different religions (relational), reflecting on narratives and memories of the past (historical), and entrusting security and safety to God (spiritual). The findings offer valuable insights for local communities and authorities in developing strategies to promote inclusive, interfaith coexistence in areas affected by past conflict.